2000
DOI: 10.1080/09637480050077158
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the nutritional quality and acceptability of sorghum-based tempe as potential weaning foods in Tanzania

Abstract: Six types of sorghum (Sorghum bicolor)-based tempe were developed by blending with various combinations and quantities of either bambara groundnut, sesame, cowpea, pigeonpea, common bean, mungbean, soybean, or groundnut (peanut) seeds. Their mixtures were then soaked and solid-state fermented by Rhizopus oligosporus to produce tempe. Soaking resulted in the loss of minerals. Mould fermentation did not change the proximate and mineral composition, but increased the in vitro protein digestibility by 10 to 14.1%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…, 1996). There are similar reports when using R. oligosporus and various substrates: mix corn/soybean (Mugula & Lyimo, 2000); soybean (Ruíz-Terán & Owens, 1996), quality protein maize and common bean (Guzmán-Uriarte et al, 2013). Dehulling chickpea decrease the content of ash and fiber mainly as a consequence of hulls containing certain minerals (calcium, phosphorus, magnesium, iron, potassium) and a high concentration of fiber (Laurena et al, 1986;Williams & Singh, 1987).…”
Section: Discussionmentioning
confidence: 68%
“…, 1996). There are similar reports when using R. oligosporus and various substrates: mix corn/soybean (Mugula & Lyimo, 2000); soybean (Ruíz-Terán & Owens, 1996), quality protein maize and common bean (Guzmán-Uriarte et al, 2013). Dehulling chickpea decrease the content of ash and fiber mainly as a consequence of hulls containing certain minerals (calcium, phosphorus, magnesium, iron, potassium) and a high concentration of fiber (Laurena et al, 1986;Williams & Singh, 1987).…”
Section: Discussionmentioning
confidence: 68%
“…In another study, six types of sorghum-based tempeh (Sorghum bicolor) were developed by mixing them with various combinations and quantities of seeds from fermentation with R. oligosporus tempeh was produced. It was observed that fermentation increased protein digestibility and amino acids such as Leu, Lys, Met, Cys, Phe, Tyr, Thr and Val were also found [14].…”
Section: Discussionmentioning
confidence: 99%
“…Sorghum grains are also popped and consumed as snacks or delicacies. Sorghum grains also partially or fully replace rice, wheat, soybean and other cereals for the production of traditional fermented foods like idli, dosa, uttapam, vada, porridges, tempeh (Lyimo 2000), gowe ) and so on, in several Asian and African Countries (Hesseltine 1979). Several traditional fermented foods like idli, dosa, dhokla, appam, and kalliappam are reportedly prepared from sorghum.…”
Section: Utilization Of Fermented Sorghum In Food and Beveragesmentioning
confidence: 99%